Investigating the influence of green human resource management practices on employee behavior and organizational commitment in Ghana’s tourism sector - Obeng, Hayford Asare; Arhinful, Richard; Mensah, Leviticus; Osei, Dennis Affum (Journal of Tourism Management Research, 2024)
This study investigates the influence of green human resource management practices on the environmentally conscious actions of employees in Ghana’s tourism sector. We collected data from 481 employees in selected hotels using a quantitative methodology through snowball sampling. We employed structural equation modelling in AMOS (Analysis of Moment Structures) version 23 for data analysis. The results revealed a statistically significant positive impact of green human resource management practices on in-role green behavior, extra-role green behavior, and green innovative work behavior. Additionally, a significant and positive correlation was identified between green human resource management practices and employees’ organizational commitment. Furthermore, organizational commitment exhibited a substantial impact on innovative green work behavior, and extra-role green behavior, and in-role green behavior. Notably, the relationship between green human resource management practices and employees’ green behavior facets was found to be mediated by organizational commitment. This study provides valuable insights for promoting environmentally friendly behaviors in the tourism industry through the implementation of green human resource management practices and fostering organizational commitment.